Physical-Mechanical Properties And Microstructure Of Breadfruit Starch Edible Films With Various Plasticizer - Cut Fatimah Zuhra Marpongahtun (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2013)
Breadfruit contains starch can be used as raw material of edible film. Research on preparation of edible films using various types of plasticizer (xylitol, sorbitol and PEG 400) has been done. The edible films were evaluated of physical-mechanical properties and microstructure. The results of this study indicate that the addition of plasticizer effect on the physical and mechanical characteristics, the edible film thickness, tensile strength and water vapor transmission rate greater using PEG 400 but percent elongation smaller than xylitol and sorbitol. Surface analysis of film was performed using Scanning Electron Microscopy (SEM) method.Keyword : Edible Film; Pati Sukun; Plasticizer; Silitol; Sorbitol ; PEG 400